Some main characteristics of alpacas’ behaviour in Szeged Zoo : Preliminary results - Prágai, Andrea; Bodnár, Ákos (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
Behaviour observations were done with four alpacas (n = 4; 1 male and 3 female) in Szeged Zoo, Hungary. Alpacas are kept in zoos and wild animal parks as exotic animals in Hungary. However, due to the producing of wool for high quality textiles, it can be expected to keep alpacas as livestock animals, too. Nowadays, special wool producing alpaca farm was founded in the east-western part of Hungary. According to this, it could be very important to observe general behavioural patterns and accommodation ability of these animals. Based on the previous results of several Hungarian zoos one can tell that alpacas have adapted well to the local climate, and also show very well results in reproduction. Due to the general behaviour of alpacas it was found, that the animals showed a very moderate behaviour in the herd. Alpacas used special vocalization and body movement to communicate during the observation. Compared to other literatures, same results were found according to the social behaviour of alpacas. They are very social and the herd should be handled as a unit by the stockperson. Alpacas have demonstrable hierarchy which can be observed right before and during feeding.